Finite element analysis of 3D transmission tower using ANSYS - Lee, Jia Wei (2015)
This thesis presents a probabilistic analysis approach applied in finite element analysis for modelling of 3D transmission tower with different parameters. The aim of this study analyse the transmission tower using Probabilistic Design System (PDS) to obtain a transmission tower that is sustainable and long term life. Furthermore, the transmission tower is also conducted under Eurocode 3 checking that is steel design. In probabilistic analysis, the results of probabilistic density function, cumulative distribution function, sample history plot, histogram plot and sensitivity plot for any input and output can be obtained. The transmission tower is analysed at 45 and 10000 simulations. The scope for this study is by using ANSYS as a software modelling process based on Finite Element Analysis and the selection of a 3D transmission tower structure based on the existing dimensions. From the Eurocode 3 checking, the structure is examined under tension, compression, bending moment resistance, shear resistance, compression buckling and lateral buckling. The green colour represents that all the members in the structure pass the checking while red colour indicates failure in the particular member. In addition, the results extracted from the simulation of 3D transmission tower model using ANSYS software are gathered and analysed to form a conclusion. There are two sources of data which are input and output parameters. There are eight input parameters which are DEADLOAD1, DEADLOAD2, DENS, ELASTIC, POISSON, TEMP, WINDLOAD1 and WINDLOAD2. In this thesis, Monte Carlo Simulation and Response Surface simulation was used to analyse the effect of parameter on the transmission tower structure. From the corresponding graphs, the values for mean, standard deviation, skewness, kurtosis, minimum and maximum relative frequency can be obtained. In conclusion, there are some limitations in this study where the literature review that is related is difficult to be found. However, it is proved that ANSYS software is capable to get results for reaction forces, deformation, axial forces, and maximum deflection by probabilistic analysis for transmission tower structures.